PENGEMBANGAN MEDIA PERMAINAN ULAR TANGGA “Self-Compassion Explorer” SEBAGAI ALAT BANTU DALAM MEMBERIKAN PEMAHAMAN SELF-COMPASSION - Zakiyyah, Najma; Wahyuningsih, Lenny; Warih Handoyo, Alfiandy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Stress is one of the psychological problems frequently experienced by adolescents due to academic, social, and developmental pressures, which may lead to anxiety and depression. One factor that can help reduce these conditions is self-compassion; however, students’ understanding of this concept remains relatively low. Therefore, this study aims to develop and evaluate the feasibility of a snakes and ladders game-based learning media called “Self-Compassion Explorer” as a tool to improve students’ understanding of self-compassion among eleventh-grade students at SMA Negeri 5 Kota Serang. This study employed a Research and Development (R&D) method using the 4D model, which consists of four stages: define, design, develop, and disseminate. The research subjects were eleventh-grade students selected using a simple random sampling technique. The research instruments included a self-compassion scale questionnaire as well as validation sheets from material experts, media experts, language experts, and practitioners. The results showed that the developed media was categorized as highly feasible based on expert evaluations, with a score of 95% from material and media experts, 91% from language experts, and 98% from practitioners. In addition, the product trial results reached 85.9% and received positive responses from students. Furthermore, there was an improvement in students’ understanding of self-compassion after using the media. In conclusion, the “Self-Compassion Explorer” game media is considered effective and feasible to be used as a guidance and counseling tool to enhance students’ understanding of self-compassion.